Honeysuckle aqueous extract and induced let-7a suppress dengue virus type 2 replication and pathogenesis. (23rd February 2017) - Lee, Ying-Ray; Yeh, Siao-Fen; Ruan, Xiao-Ming; Zhang, Hao; Hsu, Sheng-Da; Huang, Hsien-Da; Hsieh, Chang-Chi; Lin, Yee-Shin; Yeh, Trai-Ming; Liu, Hsiao-Sheng; Gan, Dai-Di
Abstract: Ethnopharmacological relevance: Honeysuckle ( Lonicera japonica Thunb.), a traditional Chinese herb, has widely been used to treat pathogen infection. However, the underlying-mechanism remains elusive. Aims of the study: To reveal the host microRNA (miRNA) profile with the anti-viral activity after honeysuckle treatment. Materials and methods: Here we reveal the differentially expressed miRNAs by Solexa ® deep sequencing from the blood of human and mice after the aqueous extract treatment. Among these overexpressed innate miRNAs both in human and mice, let-7a is able to target the NS1 region (nt 3313-3330) of dengue virus (DENV) serotypes 1, 2 and 4 predicated by the target predication software. Results: We confirmed that let-7a could target DENV2 at the predicated NS1 sequence and suppress DENV2 replication demonstrated by luciferase-reporter activity, RT-PCR, real-time PCR, Western blotting and plaque assay. ICR-suckling mice consumed honeysuckle aqueous extract either before or after intracranial injection with DENV2 showed decreased levels of NS1 RNA and protein expression accompanied with alleviated disease symptoms, decreased virus load, and prolonged survival time. Similar results were observed when DENV2-infected mice were intracranially injected with let-7a. Conclusion: We reveal that honeysuckle attenuates DENV replication and related pathogenesis in vivo through induction of let-7a expression. This study opens a new direction for prevention and treatment of DENV infection through induction of the innate miRNA let-7a by honeysuckle. Graphical abstract: